Effectiveness of interventions to support the transition home after acute stroke: a systematic review and meta-analysis - Geraldine O'Callaghan; Martin Fahy; Paul Murphy; Peter Langhorne; Rose Galvin; Frances Horgan (BMC, 2022)
Abstract Background Effective support interventions to manage the transition to home after stroke are still mostly unknown. Aim The purpose of this systematic review was to investigate the effectiveness of support interventions at transition from organised stroke services to independent living at home. Methods The Cochrane Central Register of Controlled Trials, six databases including MEDLINE and Embase, trial registries, grey literature, and Google Scholar were all searched, up to June 2021. We included randomised controlled trials enrolling people with stroke to receive either standard care or any type of support intervention from organised stroke services to home. The primary outcome was functional status. Two authors determined eligibility, extracted data, evaluated risk of bias (ROB2), and verified the evidence (GRADE). Where possible we performed meta-analyses using Risk Ratios (RR) or Mean Differences (MD). Results We included 17 studies. Support interventions led to important improvements in functional status, as determined by the Barthel Index up, to 3-months (MD 7.87 points, 95%CI:6.84 to 19.16; 620 participants; five studies; I2 = 77%). Results showed modest but significant functional gains in the medium to long-term (6-12 month follow up, MD 2.91 points, 95%CI:0.03 to 5.81; 1207 participants; six studies; I2 = 84%). Certainty of evidence was low. Support interventions may enhance quality of life for up to 3-months (MD 1.3,95% CI:0.84 to 1.76), and reduce depression (SMD -0.1,95% CI:-0.29 to − 0.05) and anxiety (MD -1.18,95% CI:-1.84 to − 0.52) at 6-12 months. Effects on further secondary outcomes are still unclear. Conclusions Incorporating support interventions as people who have experienced a stroke transition from hospital to home can improve functional status and other outcomes. Due to study heterogeneity, the essential components of effective transition of care interventions are still unknown. Adoption of core outcome sets in stroke research would allow for greater comparison across studies. Application of a development and evaluation framework engaging stakeholders would increase understanding of priorities for stroke survivors, and inform the key components of an intervention at transition from hospital-to-home. Trial registration CRD42021237397 - https://www.crd.york.ac.uk/prospero